SURVIVAL RATE OF Pangasius hypopthalmus THAT ARE IMMERSED IN CURCUMIN (Curcuma domestica V) AND WERE INFECTED BY Aeromonas hydrophila - Bertha, Agustina; Siagian, Morina Riauwaty; Lukistyowati, Iesje (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was held in June-November 2015 in Parasites and Fish Diseases Laboratory, Faculty of Fisheries and Marine Science, University of Riau Pekanbaru. This research aimed to determine survival rate of Pangasius hypopthalmus that are immersed in curcumin (Curcuma domestica V) and infected by Aeromonas hydrophila. This research used five treatment such as; Kn (negative control): were not immersed of curcumin and were not infected A. hydrophila, Kp (positive control): were not immersed of curcumin and infected by A. hydrophila), P1: immersed with curcumin 0,5g/L, P2 immersed with curcumin 0,7g/L and P3: immersed with curcumin 0,9 g/L. The fish were immersed with curcumin for two minutes each once a week and they were reared for 28 days. The result showed P1 ( immersion with curcumin solution in a dose of 0,5 g/L) were the best treatment with survival rate of 93,33% and total of leucocytes 16,1167x104 cell/mm3. It was concluded that curcumin can be used for prevention of A. hydrophilla and increase the survival rate of Pangasius hypopthalmus.Key words: Pangasius hypophthalmus, Curcumin, Aeromonas hydrophila